Screening of Phytoconstituents in Medicinal Plants and Study of Their Effect in Seed Germination - Pandey, Binjita; Sharma, Tinky; Shrestha, Bishnu Kumar; Koju, Gayatri Maiya; Thusa, Rojeena; Gupta, Dipak Kumar; Karki, Nabin (Amrit Journal, 2023)
Due to the existence of bioactive phytochemicals in plants, they have been traditionally utilized as medicine for a very long time. The present study was aimed to determine the phytoconstituents present in ten different plants collected from Katunje-Bhaktapur, Nepal. The methanol extract of the sample was used for analyzing the phytoconstituents present in the plant sample. The result revealed the existence of several phytoconstituents like alkaloid terpenoid, quinine, tannin, saponin and flavonoid in these plants. Similarly, the impact of phytoconstituents on germination of Pisum sativum seeds in water, aqueous extract, methanol, and methanol extract were analyzed. Shoot germination was retarded on all extracts.